Folic acid conjugated poly(propylene imine) dendrimer as a nanomedicine tool for targeted drug delivery: Bibliometric analysis using google scholar indexed vosviewer - Girsang, Gabriela Chelvina Santiuly; Nandiyanto, Asep Bayu Dani (Applied Research in Science and Technology, 2023)
By using bibliometric analysis and data mapping with the help of the VOSViewer program, this study aims to examine the breadth of research on the subject of folic acid-conjugated PPI dendrimers for targeted drug delivery. Data was collected from the Google Scholar scientific document database using the Harzing Publish or Perish 8 application. Journal articles containing the keywords "dendrimer," "PPI," "folic acid," and "drug delivery" that were published in the years 2018 through 2023 were used as the selection criteria for the data. The selection results in the form of 221 journal articles were analyzed and mapped. The total number of research publications has increased from 2018-2021 with the highest number of publications being 64 articles (in 2021). Research publications related to the topic experienced a decline in 2022-2023 due to the global COVID-19 pandemic. The items that are very closely related to the topic have the keywords drug delivery system, treatment, cancer, and ligand. This bibliometric analysis is expected to help researchers identify research trends and recommend future research prospects.